2019
DOI: 10.3390/ijerph16132442
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Effects of Co-Inoculation with Phosphate-Solubilizing Bacteria and N2-Fixing Bacteria on Microbial Population and Soil Amendment Under C Deficiency

Abstract: The inoculation of beneficial microorganisms to improve plant growth and soil properties is a promising strategy in the soil amendment. However, the effects of co-inoculation with phosphate-solubilizing bacteria (PSB) and N2-fixing bacteria (NFB) on the soil properties of typical C-deficient soil remain unclear. Based on a controlled experiment and a pot experiment, we examined the effects of PSB (M: Bacillus megaterium and F: Pseudomonas fluorescens), NFB (C: Azotobacter chroococcum and B: Azospirillum brasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 58 publications
(73 reference statements)
0
32
0
1
Order By: Relevance
“…According to a previous study [23], the bacterial population hit a peak at days 30-45 of incubation. Available soil N and P contents and related enzyme activity were significantly increased in co-inoculations with PSB and NFB.…”
Section: Site Description and Experimental Designmentioning
confidence: 90%
See 3 more Smart Citations
“…According to a previous study [23], the bacterial population hit a peak at days 30-45 of incubation. Available soil N and P contents and related enzyme activity were significantly increased in co-inoculations with PSB and NFB.…”
Section: Site Description and Experimental Designmentioning
confidence: 90%
“…The present study found that co-inoculation with PSB and NFB resulted in higher SAP than the others, while treatment CB achieved the highest value of SAN. Based on our previous study, synergistic effects between PSB and NFB may contribute to higher availability of soil nutrients and stimulate plant growth [23]. Several studies reported that inoculating plants with both PSB and NFB could result in higher available N and P contents in soil and nutrient uptake in plants [18,54].…”
Section: Selections Of Pgpr Could Be Considered For Multiple Purposesmentioning
confidence: 97%
See 2 more Smart Citations
“…The influences of different microbial inoculants on soil properties under controlled conditions and the practical effects on plant nutrient uptake under natural conditions have been thoroughly evaluated ( 31 33 ). In this study, we sought to investigate the dynamics of soil nutrients, plant growth, and the soil-resident bacterial community in response to successive microbial inoculations over the course of a growing season.…”
Section: Introductionmentioning
confidence: 99%